Estimation of daily proteinuria in patients with amyloidosis by using the protein-to-creatinine ratio in random urine sample - Giampaolo Talamo (Rare Tumors, 2015)
Measurement of daily proteinuria in patients with amyloidosis is recommended at the time of diagnosis for assessing renal involvement, and for monitoring disease activity. Renal involvement is usually defined by proteinuria >500 mg/day. We evaluated the accuracy of the random urine protein-to-creatinine ratio (Pr/Cr) in predicting 24 hour proteinuria in patient with amyloidosis. We com- pared results of random urine Pr/Cr ratio and concomitant 24-hour urine collections in 44 patients with amyloidosis. We found a strong correlation (Spearman’s ρ=0.874) between the Pr/Cr ratio and the 24 hour urine protein excretion. For predicting renal involvement, the optimal cut-off point of the Pr/Cr ratio was 715 mg/g. The sensitivity and specificity for this point were 91.8% and 95.5%, respectively, and the area under the curve value was 97.4%. We conclude that the random urine Pr/Cr ratio could be useful in the screening of renal involvement in patients with amyloidosis. If validated in a prospective study, the random urine Pr/Cr ratio could replace the 24 hour urine collection for the assessment of daily proteinuria and presence of nephrotic syndrome in patients with amyloidosis.